Open source software, closed source software or both: impacts on industry growth and the role of intellectual property rights - Sebastian von Engelhardt; Sushmita Swaminathan (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
There is considerable debate regarding the use of intellectual property rights (IPR) to spur innovation in the software industry. In this paper we focus on the choice of intellectual property right regimes and industry growth. We begin by developing a growth optimal mixture of open source and closed source software. This optimal scenario is then used as a basis to examine the co-existence of open and closed source software within various institutional frameworks ranging from no protection, copyright to patent protection. Such an analysis is beneficial as it enables an objective comparison of the three scenarios under the assumption that both copyrights and patents serve the purpose for which they were designed. Our analysis, based on the existence or absence of spillovers, confirms that a co-existence is growth optimal for the industry. Further, we find that the move from no protection to copyright protection increases the maximum growth rate. However, despite assuming properly functioning patents, the benefits of moving from copyright to patent protection are less clear.
Keywords: L17; L86; O31; O34; O41; O43; 330; Intellectual Property rights; software; open source; spillovers; co-existence; innovative growth; Softwareindustrie; Innovation; Spillover-Effekt; Branchenentwicklung; Open Source; Software-Recht; Immaterialgüterrechte; Theorie